The Influence of Competence and Motivation on Discipline and its Impact on Employee Performance in the Regional Secretariat - Yulmasril Yulmasril; M. Zahari; Fakhrul Rozi Yamali (Dinasti Publisher, 2024)
The goals to be accomplished in this research study are: 1) To define worker competence, inspiration, technique and also efficiency; 2) To assess the straight as well as indirect impact of proficiency along with inspiration on staff member job self-control; 3) To examine the straight as well as indirect impact of skills and also inspiration on staff member efficiency; 4) To evaluate the impact of technique on worker efficiency; & 5) To assess the impact of proficiency, as well as inspiration on technique as well as its effect on staff member efficiency. The study approach utilized is detailed as well as confirmation research study making use of main as well as additional information. The populace in this research study were 118 workers of the State Civil Service at the Regional Secretariat of West Tanjung Jabung Regency. The example was taken making use of the Slovin formula so the overall example made use of was 55 workers. The tasting method is rounded tasting. The evaluation technique makes use of the Path Analysis strategy as well as theory screening makes use of the F examination and also t examination. Information handling making use of SPSS V. 22 software application. The research study outcomes program: 1) The problem of workers at the Regional Secretariat of West Tanjung Jabung Regency can be classified as skilled encouraged as well as regimented plus high efficiency; 2) Competence as well as inspiration have a straight plus indirect impact on technique. Likewise with synchronised as well as partial theory screening, skills together with inspiration have a substantial result on technique; 3) Competence together with inspiration have a straight and also indirect result on efficiency. Likewise, with simultaneous and partial hypothesis testing, competency and motivation have a significant effect on employee performance; 4) Discipline has a significant effect on employee performance; & 5) Competence and motivation through discipline have an effect on employee performance.